Penguatan Kompetensi Guru Sekolah Menengah Pertama Melalui Assessment Diagnostik Karakter Profil Pelajar Pancasila Berbasis Digital - Mauliza; Nurhafidhah; Coryna Oktaviani (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Digital-based character diagnostic assessment is an urgency in implementing the independent curriculum and its evaluation process. Based on the facts found at SMPN 2 Idi Timur, it is found that teachers face significant challenges in preparing diagnostic assessments to evaluate the character profile of Pancasila learners. To keep up with the development of the 21st century which is dominated by the use of technology, teachers need to consider the implementation of digital-based assessments. The purpose of this activity is to increase partners' knowledge and skills about the preparation of digital-based diagnostic assessments of the character of the Pancasila learner profile. The method of implementation in this service is to provide education and workshops. The stages of the activity are divided into 3 parts, namely preparation, implementation and evaluation. The results of the activity obtained 67% of the training participants responded very satisfied, 21% were satisfied and 12% were quite satisfied with the quality of assistance provided by the service team in the preparation of digital-based pancasila student profile character diagnostic assessments. In addition, it was also obtained that by participating in the assistance, teachers as trainees felt helped in increasing their knowledge and skills about diagnostic assessment of student profile character. So it can be concluded that with this training activity, the knowledge and skills of teachers have increased.